The Incidence of Perioperative Hypersensitivity Reactions: A Single-Center, Prospective, Cohort Study. (July 2015) - Berroa, Felicia; Lafuente, Alberto; Javaloyes, Gracia; Cabrera-Freitag, Paula; de la Borbolla, Juan M.; Moncada, Rafael; Goikoetxea, Maria J.; Sanz, Maria L.; Ferrer, Marta; Gastaminza, Gabriel
Abstract : BACKGROUND: The incidence of perioperative hypersensitivity reactions, which can be life-threatening, ranges from 1 in 20, 000 to 1 in 1361. These reactions are usually classified as IgE or non-IgE mediated. The aim of this study was to determine the incidence of allergic reactions during general anesthesia in our hospital, to establish the incidence of the allergic reactions for each drug used, to assess the frequency of IgE-mediated reactions in even mild reactions, and to compare the degree of agreement between anesthesiologist suspicion and allergy diagnosis. METHODS: We included patients diagnosed with a clinical hypersensitivity reaction during a procedure under general anesthesia over a 30-month period (February 2008 to August 2010). Plasma histamine and serum tryptase concentrations were determined in these patients. We performed skin tests to diagnose the causative agent. Data from the hospital electronic prescribing system were collected to determine the ratio of reactions for each drug. RESULTS: During the study period, 16, 946 anesthetic procedures were performed (53% involved males; mean age, 51.6 years). Forty-four perianesthetic reactions were recorded, and the ratio of reactions was 1 in 385 operations (95% confidence interval, 1/529–1/287). Twenty-five reactions (25/44; 57%) occurred during the induction of anesthesia. Twenty-one reactions (21/44; 48%) were mild, involving only skin, and 23 of 44 (52%) were anaphylactic reactions. Four of 10 patients who had only a rash experienced IgE-mediated reactions. Five surgeries (11%) were suspended because of the severity of the reactions. Fifteen reactions (15/30; 50%) were IgE mediated, and, in 2 of 30 (7%), a non-IgE agent was found (cold urticaria and nonsteroidal anti-inflammatory drug intolerance). The ratio of reactions for each drug was as follows: protamine, 1 in 468; cisatracurium, 1 in 1388; amoxicillin-clavulanate, 1 in 1968; atracurium, 1 in 2039; and dipyrone, 1 in 3159. CONCLUSIONS: Perioperative reactions are more common than previously reported. Mild hypersensitivity perioperative reactions—involving only skin—should be considered in evaluating patients because a substantial number of these reactions are IgE mediated. Abstract : Published ahead of print April 21, 2015